Isolation and identification of indigenous lactic acid bacteria from North Sumatra river buffalo milk - Heni Rizqiati; Cece Sumantri; Ronny Rachman Noor; E. Damayanthi; E. I. Rianti (Jurnal Ilmu Ternak dan Veteriner, 2015)
Buffalo milk is a source of various lactic acid bacteria (LAB) which is potential as culture starter as well as the probiotic. This study was conducted to isolate and identify LAB from indigenous North Sumatra river buffalo milk. Lactic acid bacteria was isolated and grown in medium De Man Rogosa Sharpe Agar (MRSA). The isolation was conducted to obtain pure isolate. The identification of  LAB was studied in terms of morphology, physiology, biochemistry and survival on low pH. Morphology tests were conducted by Gram staining and cell forming; physiology tests were conducted for growing viability at pH 4.5 and temperature at 45oC; whereas biochemistry tests were conducted for CO2, dextran and NH3 productions. Determination of LAB species was conducted using Analytical Profile Index (API) test CHL 50. Results of identification showed that 41 isolates were identified as LAB with Gram-positive, catalase-negative, rod and round shaped characteristics. Resistance test done to low pH (pH 2) for the lactic acid bacteria showed decrease of bacteria viability up to1.24±0.68 log cfu/ml. The resistant isolates at low pH were L12, L16, L17, L19, L20, M10, P8, S3, S19 and S20. Identification with API test CHL 50 for 10 isolates showed that four isolates were identified as Lactobacillus plantarum, L. brevis, L. pentosus and Lactococuslactis.